Le tradizioni come identità: la Baìo di Sampeyre - Olcese, Gianluca (My University, 2012)
During the last Baìo in 2007, I interpreted carnival as an occasion to investigate popular traditions. Agricultural feasts have been present since ancient times, sometimes hidden behind the veil of other meanings: today they represent a way to allow the present society to feel itself as a continuation of the past. The communities of small local areas show a representation of their identity through ancient rituals – like manifestations, such as the Baìo – to sew their relationships with the modern territory. Those rituals also demonstrate several, and sometimes unexpected, connections with different cultures of the present and the past.
Keywords: traditions; popular feasts; continuity; folk culture